2015
DOI: 10.1155/2015/675437
|View full text |Cite
|
Sign up to set email alerts
|

Strong Manual Acupuncture Manipulation Could Better Inhibit Spike Frequency of the Dorsal Horn Neurons in Rats with Acute Visceral Nociception

Abstract: Afferent impulses from visceral nociception can be regulated by acupuncture at spinal cord level; however, the effects of different manual acupuncture (MA) manipulations on the afferent impulses are still unknown. Here, we analyzed the spike frequency of excitatory gastric-related wide dynamic range (WDR) neurons in spinal dorsal horn (SDH) following acute gastric distension (GD) in rats and compared their responses to MA manipulations with four different frequencies (0.5, 1, 2, and 3 Hz) at Zusanli (ST36). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…ST 36 is a lower confluent acupoint of the meridians of the stomach. It is innervated by the same segment of the rectum and colon and involved in the treatment of gastrointestinal diseases 14,18,22. The lumbar spinal WDR neurons receive ipsilateral ST36 afferent input 23.…”
Section: Discussionmentioning
confidence: 99%
“…ST 36 is a lower confluent acupoint of the meridians of the stomach. It is innervated by the same segment of the rectum and colon and involved in the treatment of gastrointestinal diseases 14,18,22. The lumbar spinal WDR neurons receive ipsilateral ST36 afferent input 23.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is one of the most popular and safest CAM therapies [25] as part of ancient Traditional Chinese Medicine (TCM) with a history of more than 4000 years [31]. It is a traditional healing technique involving the insertion of fine, solid, metallic needles into targeted sites called "acupoints" on the body wall to achieve therapeutic outcomes [31][32][33]. After insertion, the needles are usually stimulated manually with slight twisting back and forth and with gentle movements up and down (manual acupuncture, MA), or are stimulated by the sequential electrical impulses delivered by an electric microcurrent device (electroacupuncture, EA) [31,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further research is necessary in order to determine whether the gentle MA is more effective than the strong MA in other diseases or conditions. Nevertheless, in our previous study, it was found that the strong MA exhibited greater effects on acute visceral nociception than the gentle MA [29]. Tian et al [30] study showed that high-frequency electroacupuncture induced inhibiting effects on the activation of abnormal astrocytes to a greater extent compared with low-frequency electroacupuncture through down-regulation of COX-2, β -catenin, and NK-1R expression, and thus alleviating the inflammation and poststroke pain.…”
Section: Discussionmentioning
confidence: 99%